Social support, functional outcome and quality of life among stroke survivors in an urban area. (2019) - Butsing, Nipaporn; Tipayamongkholgul, Mathuros; Ratanakorn, Disya; Suwannapong, Nawarat; Bundhamcharoen, Kanitta
Abstract: Sophisticated medical technologies can prolong a stroke patient's life but not always their quality of life (QoL) due to poor functional outcomes. Social support can theoretically assist a patient's adaptation to life after stroke and improve their QoL, but existing findings are inconclusive. This inconclusiveness is especially found in large cities where family and social bonding can be scarce. We conducted a hospital-based, cross-sectional study among 358 stroke patients to identify the effects of social support and functional outcome on QoL and its domains. The study took place in Bangkok, Thailand between July and December 2016. Data were collected by personal interview using a structured questionnaire that included the Short-Form WHO Quality of Life Instrument (WHOQOL-BREF) and by review of medical records. A hierarchical linear regression method was used to analyze data. The mean age of stroke respondents was 66.0 years ( SD 13.5 years), and half were male. The mean total QoL score for patients was 68.6 ( SD 15.2). Hierarchical multiple regression analysis found emotional support significantly impacted QoL in every domain ( p s < .05) when all included variables were controlled for. To improve the quality of life among stroke survivors, health personnel and family members should provide not only physical assistance but also psychological support.